Zinc coordination polymer catalyst for depolymerizing polylactic acid to recover lactide as well as microwave-assisted preparation method and application of zinc coordination polymer catalyst

The zinc-coordinated polymer catalyst prepared under microwave conditions has solved the problems of low catalyst activity, long depolymerization time, high temperature and low recovery rate in the prior art, and achieved efficient, low temperature and short-term polylactic acid depolymerization recovery lactide monomer, with good application prospects.

CN119529301AActive Publication Date: 2025-02-28CHANGZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411623414.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-28
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

In the prior art, zinc, tin and strong alkali catalysts are not active when catalyzing polylactic acid depolymerization and recovery of lactide monomers, the activity is low, the depolymerization time is long, the depolymerization temperature is high, the monomer recovery rate is low, and the catalyst is not recyclable, resulting in low recycling efficiency of PLA waste.

Method used

A zinc coordination polymer catalyst with high activity was prepared using a zinc coordination polymer catalyst prepared under microwave conditions. By mixing zinc salt, formate and organic solvents and reacting under microwave reaction conditions, a zinc coordination polymer catalyst with high activity was prepared for catalyzing polylactic acid depolymerization and recovery of lactide monomers.

Benefits of technology

The efficient recovery of catalytic polylactic acid depolymerization has been achieved. The purity of monomer lactide reaches 99.5%, the recovery rate can reach 99.0%, and the reaction temperature is low, the reaction time is short and the catalyst is small, which has good application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005134049060000011
    Figure HDA0005134049060000011
  • Figure HDA0005134049060000012
    Figure HDA0005134049060000012
  • Figure HDA0005134049060000021
    Figure HDA0005134049060000021
Patent Text Reader

Abstract

The invention belongs to the technical field of waste polylactic acid monomer recovery, and discloses a zinc coordination polymer catalyst for depolymerizing polylactic acid to recover lactide and a microwave-assisted preparation method and application thereof.The preparation method comprises the steps that zinc salt, formate and an organic solvent are mixed and subjected to a reaction under the microwave condition, and a reaction product is obtained; the zinc coordination polymer catalyst is obtained through filtration and separation, and the repeating structural unit of the zinc coordination polymer catalyst is [Zn (HCOO) 2]. Compared with the prior art, the method is simple to operate, advanced in process, short in reaction time and high in yield. The zinc coordination polymer has good activity in catalysis of polylactic acid depolymerization, the purity of the monomer lactide is 99.5%, the recovery rate can reach 99.0%, and compared with zinc oxide, zinc chloride and other catalysts, the zinc coordination polymer has the advantages of low reaction temperature, short reaction time and small catalyst dosage in the catalytic depolymerization process, and has good application prospects. The method has a good application prospect in the field of waste polylactic resin monomer recovery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of waste polylactic acid monomer recovery, and specifically relates to a zinc coordination polymer catalyst for polylactic acid monomer recovery and a microwave-assisted preparation and application thereof. Background Art

[0002] Polylactic acid (PLA) is a biodegradable polymer polyester material with excellent biocompatibility, processability and mechanical properties. In addition to being used in biomedical fields such as surgical sutures, drug sustained-release packaging agents and tissue repair materials, it can also be used in disposable items such as tableware and food packaging materials, as well as agricultural covering films, textiles and 3D printing. With the widespread application of PLA in various fields, although it has the ability to degrade in natural environments such as water and soil, its degradation cycle is relatively long, and the large accumulation of PLA waste in the environment may cause new pollution. Therefore, it is of great significance to recycle lactide monomers from PLA waste.

[0003] Catalytic depolymerization of polylactic acid to recover lactide monomer is a very effective method for recycling PLA waste. Catalysts play a vital role. The most common catalysts are zinc, tin and strong base catalysts. Wang Qinggang et al. used bipyridyl zinc chloride as a catalyst in the process of catalytic depolymerization of PLA to recover lactide monomer. After 9 hours of reaction at 200°C and vacuum degree of 1 mPa, the lactide monomer recovery rate was 97.2% (CN115160287); Liu Xiong et al. used stannous octoate as a catalyst to depolymerize PLA and found that after 1.5 hours of vacuum distillation at 195°C, the lactide monomer yield could reach 96.5% (CN115403554); Xu Guangqiang et al. used 1,5,7-triazabicyclo[4.4.0]dec-5-ene as a catalyst. PLA was distilled at a higher temperature (220°C) for 4 hours before the reaction ended. The lactide recovery rate was 98.0% (CN115160288). The above-mentioned zinc, tin and strong base homogeneous catalysts are not very active, have a long depolymerization time, a high depolymerization temperature, a low monomer recovery rate and the catalyst is not recyclable. In 2022, Hou Cuiping et al. used molecular sieve SBA-15 loaded with zinc oxide heterogeneous catalyst to depolymerize PLA. After 4 hours of vacuum distillation at 200°C, the lactide monomer recovery rate was 89.0%, and the recovered catalyst remained unchanged after reuse (CN118026990). Therefore, it is of great scientific significance and application value to research and develop recyclable and highly active depolymerization catalysts for the depolymerization of PLA waste to recover lactide.

[0004] Coordination polymers are a new type of inorganic-inorganic hybrid material that is self-assembled by coordination between metal ions and organic ligand molecules. They have structural diversity, tunability, and unsaturated metal active sites. They have been widely used in alkylation reactions, condensation reactions, transesterification reactions, polymerization reactions, and various oxidation reactions. Coordination polymers, especially zinc-based coordination polymers with good biocompatibility, have been widely used in catalyzing the ring-opening polymerization of lactide to prepare PLA. However, there are no reports on the application of coordination polymers to catalyze the depolymerization of biodegradable polyesters. The research and development of new coordination polymers to quickly and efficiently catalyze the depolymerization of waste PLA to recover monomers has a broad application space and also provides a new direction for the research on monomer recycling of PLA waste. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] The purpose of the present invention is to provide a method for preparing a zinc coordination polymer catalyst by using microwaves and its application in depolymerizing polylactic acid to recover lactide.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] A method for preparing a zinc coordination polymer catalyst comprises:

[0009] A zinc salt, a formate and an organic solvent are mixed and reacted under microwave conditions, and a zinc coordination polymer catalyst is obtained after separation by filtration, wherein the repeating structural unit is [Zn(HCOO)2];

[0010] The microwave conditions include: microwave output power of 200-800W, microwave frequency of 2000-3000MHz; reaction conditions include: reaction temperature of 100-180°C, reaction time of 5-90 minutes.

[0011] Furthermore, the zinc salt includes one or more of zinc chloride, zinc acetate, and zinc nitrate.

[0012] Furthermore, the formate includes one or more of potassium formate, calcium formate, sodium formate and magnesium formate.

[0013] Furthermore, the molar ratio of the zinc salt to the formate is 1:2-6.

[0014] Furthermore, the solvent is one of ethanol, methanol, N,N-dimethylformamide, N-methylformamide, or a mixed solution.

[0015] Furthermore, the amount of the solvent is 4 to 60 ml per 1 mmol of the zinc salt.

[0016] A zinc coordination polymer catalyst is prepared by the method as described above.

[0017] An application of a zinc coordination polymer catalyst, wherein the catalyst is applied to catalyze the depolymerization of polylactic acid to recover lactide monomer, comprising:

[0018] The zinc coordination polymer and polylactic acid were first mixed in a ball mill for 20 minutes, and then the mixture was put into a Schlenk reaction tube, and the lactide monomer was collected by vacuum distillation.

[0019] Wherein, the reaction conditions include: reaction temperature of 175°C to 215°C, reaction time of 10 to 300 minutes, and vacuum degree of 5 to 1000 Pa.

[0020] Furthermore, the mass ratio of the polylactic acid to the zinc coordination polymer is 100:0.1-10, the purity of the monomer lactide is 99.5%, and the recovery rate can reach 99.0%, which has good application prospects in the field of waste polylactic acid resin monomer recovery.

[0021] Compared with the prior art, the present invention has the following characteristics:

[0022] The zinc coordination polymer preparation method of the present invention is simple, has advanced technology, short reaction time and a yield of up to 96.1%. The zinc coordination polymer catalyzes the depolymerization of polylactic acid with good activity, the purity of the monomer lactide is 99.5%, and the recovery rate can reach 99.0%. Compared with catalysts such as zinc oxide and zinc chloride, it has the advantages of low reaction temperature, short reaction time and small amount of catalyst in the catalytic depolymerization process, and has good application prospects in the field of waste polylactic acid resin monomer recovery. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a schematic diagram of the infrared spectrum of the zinc coordination polymer in Example 1;

[0024] Figure 2 This is a schematic diagram of the diffraction of the zinc coordination polymer powder in Example 1;

[0025] Figure 3 This is a schematic diagram of the thermogravimetric properties of the zinc coordination polymer in Example 1;

[0026] Figure 4 This is a schematic diagram of the H NMR spectrum of lactide recovered from the depolymerization of polylactic acid catalyzed by the zinc coordination polymer in Example 10. DETAILED DESCRIPTION

[0027] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0028] Example 1

[0029] A method for preparing a zinc coordination polymer catalyst using a microwave method:

[0030] Zinc chloride (136 mg, 1 mmol), potassium formate (336 mg, 4 mmol) and N,N-dimethylformamide (25 ml) were added to a 100 ml polytetrafluoroethylene-lined reactor, and then the reactor was placed in a microwave reactor, and the microwave output power was set to 400 W, the microwave frequency was set to 2450 MHz, and the reaction temperature was set to 140°C. The reaction was terminated after 30 minutes, and the mixture was filtered and dried to obtain a white powder with a yield of 96.1% (149.2 mg, based on Zn).

[0031] Infrared data (KBr, cm -1 ):3236m,1637s,1617s,1558m,1461m,1418m,1384m,1338m,1188w,1153m,1043w,848w,799w,617m,514m,447m, see Figure 1 . (Instrument model: Nicolet ESP 460)

[0032] Example 2

[0033] A method for preparing a zinc coordination polymer catalyst by microwave method,

[0034] Zinc chloride (136 mg, 1 mmol), potassium formate (504 mg, 6 mmol) and N,N-dimethylformamide (60 ml) were added to a 100 ml polytetrafluoroethylene-lined reactor, and then the reactor was placed in a microwave reactor, and the microwave output power was set to 400 W, the microwave frequency was set to 2450 MHz, and the reaction temperature was set to 180°C. The reaction was terminated after 30 minutes, and the mixture was filtered and dried to obtain a white powder with a yield of 89.2% (138.3 mg, based on Zn).

[0035] Example 3

[0036] A method for preparing a zinc coordination polymer catalyst by microwave method,

[0037] Zinc acetate (183 mg, 1 mmol), calcium formate (520 mg, 4 mmol) and N,N-dimethylformamide (25 ml) were added to a 100 ml polytetrafluoroethylene-lined reactor, and then the reactor was placed in a microwave reactor, and the microwave output power was set to 200 W, the microwave frequency was set to 2000 MHz, and the reaction temperature was set to 100°C. The reaction was terminated after 90 minutes, and the mixture was filtered and dried to obtain a white powder with a yield of 51.6% (73.2 mg, based on Zn).

[0038] Example 4

[0039] A method for preparing a zinc coordination polymer catalyst by microwave method,

[0040] Zinc nitrate (189 mg, 1 mmol), sodium formate (272 mg, 4 mmol) and N,N-dimethylformamide (25 ml) were added to a 100 ml polytetrafluoroethylene-lined reactor, and then the reactor was placed in a microwave reactor, and the microwave output power was set to 800 W, the microwave frequency was set to 3000 MHz, and the reaction temperature was set to 140°C. The reaction was terminated after 30 minutes, and the mixture was filtered and dried to obtain a white powder with a yield of 83.3% (128.9 mg, based on Zn).

[0041] Example 5

[0042] A method for preparing a zinc coordination polymer catalyst by microwave method,

[0043] Zinc chloride (136 mg, 1 mmol), potassium formate (168 mg, 2 mmol) and N,N-dimethylformamide (4 ml) were added to a 100 ml polytetrafluoroethylene-lined reactor, and then the reactor was placed in a microwave reactor, and the microwave output power was set to 400 W, the microwave frequency was set to 2450 MHz, and the reaction temperature was set to 180°C. The reaction was terminated after 5 minutes of reaction, and the mixture was filtered and dried to obtain a white powder with a yield of 65.5% (101.1 mg, based on Zn).

[0044] Example 6

[0045] A method for preparing a zinc coordination polymer catalyst by microwave method,

[0046] Zinc chloride (136 mg, 1 mmol), magnesium formate (600 mg, 4 mmol) and N-methylformamide (25 ml) were added to a 100 ml polytetrafluoroethylene-lined reactor, and then the reactor was placed in a microwave reactor, and the microwave output power was set to 400 W, the microwave frequency was set to 2450 MHz, and the reaction temperature was set to 140°C. The reaction was terminated after 30 minutes, and the mixture was filtered and dried to obtain a white powder with a yield of 74.4% (114.9 mg, based on Zn).

[0047] Example 7

[0048] A method for preparing a zinc coordination polymer catalyst by microwave method,

[0049] Zinc chloride (136 mg, 1 mmol), calcium formate (520 mg, 4 mmol) and methanol (25 ml) were added to a 100 ml polytetrafluoroethylene-lined reactor, and then the reactor was placed in a microwave reactor, and the microwave output power was set to 200 W, the microwave frequency was set to 2450 MHz, and the reaction temperature was set to 140°C. The reaction was terminated after 30 minutes, and the mixture was filtered and dried to obtain a white powder with a yield of 79.6% (122.7 mg, based on Zn).

[0050] Example 8

[0051] A method for preparing a zinc coordination polymer catalyst by microwave method,

[0052] Zinc acetate (183 mg, 1 mmol), potassium formate (336 mg, 4 mmol) and ethanol (25 ml) were added to a 100 ml polytetrafluoroethylene-lined reactor, and then the reactor was placed in a microwave reactor, and the microwave output power was set to 800 W, the microwave frequency was set to 2450 MHz, and the reaction temperature was set to 140°C. The reaction was terminated after 30 minutes, and the mixture was filtered and dried to obtain a white powder with a yield of 91.1% (141.4 mg, based on Zn).

[0053] Comparative Example 1: Effect of Microwave Treatment

[0054] A method for preparing a zinc coordination polymer catalyst:

[0055] Zinc chloride (136 mg, 1 mmol), potassium formate (336 mg, 4 mmol) and N,N-dimethylformamide (25 ml) were added to a 100 ml polytetrafluoroethylene-lined reactor, and then the reactor was placed in an oven at a reaction temperature of 140°C. The reaction was terminated after 3 days, filtered and dried to obtain a zinc coordination polymer white powder with a yield of 35.8% (53.2 mg, based on Zn).

[0056] Comparative Example 2

[0057] A method for preparing a zinc coordination polymer catalyst:

[0058] Zinc chloride (136 mg, 1 mmol), potassium formate (336 mg, 4 mmol) and N,N-dimethylformamide (25 ml) were added to a 50 ml four-necked flask. The reaction temperature was 140°C and the reaction was terminated after mechanical stirring for 3 days. No zinc coordination polymer was obtained.

[0059] Example 9

[0060] Characterization of the zinc coordination polymer catalyst of Example 1.

[0061] (1) Phase purity characterization of zinc coordination polymer catalysts

[0062] The phase purity of zinc coordination polymer can be characterized by X-ray powder diffractometer. The diffraction pattern of zinc coordination polymer catalyst prepared by microwave method was measured by Rigaku D / Max-2500 of Japan Science and Technology, and compared with the theoretical value (CuKα rake, fixed monochromator, tube voltage 40kV, tube current 100mA, scanning rate 8° / min). The results show that the zinc coordination polymer prepared by microwave method has similar diffraction peaks to the theoretical value, indicating that it has reliable phase purity, which provides guarantee for its application as catalytic depolymerization of polylactic acid. Figure 2 : Schematic diagram of powder diffraction of zinc coordination polymer.

[0063] (2) Characterization of thermal stability of zinc coordination polymer catalysts

[0064] The thermal stability of zinc coordination polymers can be characterized by thermogravimetric analyzer. The zinc coordination polymers prepared by microwave method were measured by German NETZSCH / TG209F3 thermogravimetric analyzer (nitrogen atmosphere, temperature range of 50-600℃, heating rate of 10℃ / min). The thermogravimetric curve shows that the coordination framework of zinc coordination polymers prepared by microwave method stabilizes to 225℃, then begins to collapse and loses weight rapidly to 340℃, and then the weight loss becomes slow. Figure 3 : Schematic diagram of thermogravimetric analysis of zinc coordination polymer.

[0065] Example 10

[0066] The performance of the zinc coordination polymer prepared by the microwave method in Example 1 in catalyzing the depolymerization of polylactic acid to recover lactide monomer was studied.

[0067] Polylactic acid (L-polylactic acid (PLLA)) (4 g) and zinc coordination polymer (0.2 g) were mixed in a ball mill for 20 minutes, and the mixture was then put into a Schlenk reaction tube, heated to 190°C, and distilled under reduced pressure (30 Pa) for 60 minutes to collect the depolymerization product. After drying, 3.96 g of lactide monomer was obtained with a purity of 99.5% and a yield of 99.0%.

[0068] Embodiment 11

[0069] The zinc coordination polymer prepared by microwave method in Example 1 is used to catalyze the depolymerization of polylactic acid to recover lactide. Compared with Example 10, the only difference is that the reaction temperature is 175° C. and the reaction time is 300 minutes; the rest is the same as Example 10.

[0070] 2.16 g of lactide monomer was obtained with a purity of 96.3% and a yield of 54.2%.

[0071] Example 12

[0072] The zinc coordination polymer prepared by microwave method in Example 1 was used to catalyze the depolymerization of polylactic acid to recover lactide. Compared with Example 10, the only difference was that the reaction temperature was 215° C. and the reaction time was 10 minutes; the rest was the same as Example 10.

[0073] 2.96 g of lactide monomer was obtained with a purity of 98.0% and a yield of 74.4%.

[0074] Embodiment 13

[0075] The zinc coordination polymer prepared by microwave method in Example 1 was used to catalyze the depolymerization of polylactic acid to recover lactide, and the only difference compared with Example 10 was that the amount of zinc coordination polymer used was 0.4 g; the rest was the same as Example 10. 3.68 g of lactide monomer was obtained, with a purity of 99.1% and a yield of 92.1%.

[0076] Embodiment 14

[0077] The zinc coordination polymer prepared by microwave method in Example 1 was used to catalyze the depolymerization of polylactic acid to recover lactide. Compared with Example 10, the only difference was that the amount of zinc coordination polymer used was 0.004 g and the vacuum degree was 5 Pa; the rest was the same as Example 10.

[0078] 2.56 g of lactide monomer was obtained with a purity of 97.6% and a yield of 64.1%.

[0079] Embodiment 15

[0080] The zinc coordination polymer prepared by microwave method in Example 1 was used to catalyze the depolymerization of polylactic acid to recover lactide. Compared with Example 10, the only difference was that the vacuum degree was 1000 Pa and the reaction time was 300 minutes; the rest was the same as Example 10.

[0081] 3.28 g of lactide monomer was obtained with a purity of 98.4% and a yield of 82.3%.

[0082] Example 16

[0083] Characterization of lactide monomer purity.

[0084] The purity of the lactide monomer was characterized by a nuclear magnetic resonance spectrometer, and the purity of the lactide monomer was determined by a German AVANCE III 400M nuclear magnetic resonance spectrometer (with tetramethylsilane (TMS, δ = 0 ppm) as the internal standard and deuterated chloroform (CDCl3, δ = 7.26 ppm) as the solvent). The hydrogen nuclear magnetic resonance spectrum showed that the lactide monomer recovered from the depolymerization of polylactic acid catalyzed by the zinc coordination polymer had a very high purity. For example, the lactide monomer recovered in Example 10 was purified by 1 The purity was 99.5% according to HNMR quantitative analysis. Figure 4 : Schematic diagram of H NMR spectrum of lactide recovered from depolymerization of polylactic acid catalyzed by zinc coordination polymer.

[0085] Comparative Example 3

[0086] Zinc formate is used to catalyze the depolymerization of polylactic acid to recover lactide, and the catalytic reaction process is the same as that in Example 10.

[0087] 0.64 g of lactide monomer was obtained with a purity of 90.5% and a yield of 16.7%.

[0088] Comparative Example 4

[0089] Zinc acetate is used to catalyze the depolymerization of polylactic acid to recover lactide, and the catalytic reaction process is the same as that in Example 10.

[0090] 0.92 g of lactide monomer was obtained with a purity of 92.7% and a yield of 23.4%.

[0091] Comparative Example 5

[0092] Zinc nitrate is used to catalyze the depolymerization of polylactic acid to recover lactide, and the catalytic reaction process is the same as that in Example 10.

[0093] 1.24 g of lactide monomer was obtained with a purity of 95.2% and a yield of 31.3%.

[0094] Comparative Example 6

[0095] Zinc oxide is used to catalyze the depolymerization of polylactic acid to recover lactide, and the catalytic reaction process is the same as that in Example 10.

[0096] 2.56 g of lactide monomer was obtained with a purity of 97.5% and a yield of 64.5%.

[0097] Comparative Example 7

[0098] Zinc lactate is used to catalyze the depolymerization of polylactic acid to recover lactide, and the catalytic reaction process is the same as that in Example 10.

[0099] 1.72 g of lactide monomer was obtained with a purity of 96.0% and a yield of 43.1%.

[0100] Comparative Example 8

[0101] Zinc chloride is used to catalyze the depolymerization of polylactic acid to recover lactide, and the catalytic reaction process is the same as that in Example 10.

[0102] 1.92 g of lactide monomer was obtained with a purity of 96.2% and a yield of 48.0%.

[0103] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a zinc coordination polymer catalyst, characterized in that: The method comprises: mixing zinc salt, formate and organic solvent, reacting under microwave conditions, and obtaining a zinc coordination polymer catalyst after filtering and separation. The repeating structural unit of the zinc coordination polymer catalyst is [Zn(HCOO)2].

2. The method for preparing a zinc coordination polymer catalyst according to claim 1, characterized in that: The microwave conditions include: microwave output power of 200-800W, microwave frequency of 2000-3000MHz; reaction conditions include: reaction temperature of 100-180°C, reaction time of 5-90 minutes.

3. The method for preparing the zinc coordination polymer catalyst according to claim 1, characterized in that: The zinc salt includes one or more of zinc chloride, zinc acetate, and zinc nitrate; the formate includes one or more of potassium formate, calcium formate, sodium formate, and magnesium formate.

4. The method for preparing the zinc coordination polymer catalyst according to claim 1, characterized in that: The molar ratio of the zinc salt to the formate is 1:2-6.

5. The method for preparing the zinc coordination polymer catalyst according to claim 1, characterized in that: The organic solvent is one or more mixed solvents selected from ethanol, methanol, N,N-dimethylformamide and N-methylformamide.

6. The method for preparing the zinc coordination polymer catalyst according to claim 1, characterized in that: The amount of the solvent corresponding to 1 mmol of the zinc salt is 4 to 60 ml.

7. A zinc coordination polymer catalyst, characterized in that The zinc coordination polymer catalyst is prepared by the method according to any one of claims 1 to 6.

8. The use of the zinc coordination polymer catalyst as claimed in claim 7, characterized in that: The zinc coordination polymer catalyst is used for catalyzing the depolymerization of polylactic acid to recover lactide monomer.

9. The use of the zinc coordination polymer catalyst as claimed in claim 8, characterized in that: The process is carried out according to the following steps: the zinc coordination polymer and polylactic acid are first mixed in a ball mill, and then the mixture is put into a reaction device, and lactide monomers are collected by vacuum distillation.

10. The use of the zinc coordination polymer catalyst according to claim 9, characterized in that: The mass ratio of polylactic acid to zinc coordination polymer is 100:0.1-10; the reaction conditions include: reaction temperature of 175-215°C, reaction time of 10-300 minutes, and vacuum degree of 5-1000 Pa.

Citation Information

Patent Citations

  • Preparation method of zinc oxide nanorod / carbon cloth reinforced resin friction material

    CN107778502A

  • Rapid metal organic framework molecule synthesis method

    US20090131643A1

  • A new preparation method of porous coordination polymer compounds composed of zinc ion and carboxylates

    WO2007102676A1